Pemberdayaan Masyarakat Kampung Heberima Kabupaten Jayawijaya Povinsi Papua dalam Upaya Pengembangan Kampung Agrowisata - Rosalina Mabel; Dominikus Wetapo; Ronald Tugiarek Huby; Narodi Wenda; Agonius Wenda; Marsel Matuan; Meti Wenda; Pita Lokbere; Noria Kudligagal; Koris Kogoya; Wetepina Heluka; Endius Tabuni; Yas Kogoya; Anjeli Gombo; Ben Elopere; Kaiben Wenda; Sumiyati Tuhuteru (Jurnal Pengabdian Masyarakat (abdira), 2022)
Local community development is a process aimed at creating social and economic progress for the community to be directly involved in empowering farmers in Heberima Village, Jayawijaya Regency with the aim of helping farmers develop and cultivate their land to be productive and able to prosper farmers. In addition, it can also directly develop organic farming systems that have been implemented for a long time. The method of implementations this activity is carried out by socialization, mentoring, training and workshops. This activity was carried out in July-October 2021. The results of the implementation of this activity have a positive impact and good learning for students, institutions, partners and local governments in processing unproductive land into productive land and increasing farmers' income by aligning agricultural and tourism activities. The percentage of achievement of the results of service activities is 80% of farmers as land owners who are very enthusiastic in implementing the intended PHP2D activities.